Particulate migration behavior and its mechanism during selective laser melting of TiC reinforced Al matrix nanocomposites. (5th October 2015) - Yuan, Pengpeng; Gu, Dongdong; Dai, Donghua
Abstract : Graphical abstract: Highlights: Model simulating fluid flow and particles migration behavior was established. Influence of LEPUL on melt pool dynamics and particles rearrangement was studied. Physical mechanism of the movement of reinforcing particles was disclosed. Experimental study was performed to validate the obtained results in simulation. Abstract: A transient three-dimensional model for describing fluid flow characteristics and particles migration behavior within the melt pool during selective laser melting (SLM) of TiC/AlSi10Mg nanocomposites was developed. The powder-solid transition, variation of thermophysical properties, and surface tension were considered in the model. The influence of laser energy per unit length (LEPUL) on heat and mass transfer, melt pool dynamics, and particles rearrangement was investigated. It showed that the Marangoni convection became more vigorous with an increase of LEPUL, accordingly enhancing the thermal capillary force. The high laser energy input induced a sufficient liquid formation and an improved wettability, lowering the friction force exerting on TiC solids. Under this condition, the reinforcing particles can be well mixed within the matrix. The experimental study on the distribution state of TiC reinforcement in the SLM-processed Al matrix was performed. The results validated that the dispersion of TiC reinforcement changed from a severe aggregation to a uniform dispersion in the matrix with the increase of LEPUL. The TiC reinforcement experienced a microstructural variation from the standard nanoscale structure with a mean particle size of 70–90 nm to the relatively coarsened submicron morphology with an average particle size of 134 nm as LEPUL increased.